The Effect of Jigsaw Type Cooperative Learning Model with Mind Mapping Assistance in Improving Critical Thinking Skills of Elementary School Students - Yuniar, Hani Astrid; Yuliyanto, Aan; Sofiasyari, Irma; Muzfirah, Suci; Noviyanto, Tommy; Faturochman, (International Conference on Elementary Education, 2025)
Education is an essential asset for the nation, especially at the primary school level, where the foundation of skills and knowledge is built for the next level. However, many students face low critical thinking skills, have difficulty analyzing information, evaluating arguments, and making rational decisions. This becomes an obstacle in learning that requires in-depth understanding, including in Social Sciences (IPS). This literature review used an integrative review design that aims to analyze the effect of applying the Jigsaw-type cooperative learning model with the help of mind mapping on students' critical thinking skills in learning Social Sciences in elementary schools. The findings from this study indicate that learners are capable of sharing their thoughts, being engaged, posing questions effectively, communicating proficiently, showing a strong desire to understand the subject matter, and putting in effort. This enables them to think critically and enhance their academic performance. By utilizing interactive and cooperative teaching strategies like jigsaws and mind mapping, the aim is for students to be more involved in their education and cultivate critical thinking abilities necessary for tackling everyday challenges